SLOW-ACTING ANTI-ARTHROSIS MEDICATIONS FOR THE TREATMENT OF OSTEOARTHRITIS - M. S. SVETLOVA (Медицинский совет, 2016)
The article tells about the epidemiological and pathogenetic aspects of osteoarthritis, current treatment approaches, primarily highlighting the slow-acting anti-arthrosis medications, chondroitin sulphate, glucosamine and their combinations. There are results of recent trials which studied the effect of the above mentioned medications on the symptoms and progression of osteoarthritis, as well as several pleiotropic effects of the combination of chondroitin sulfate and glucosamine.